Sensitivity studies toward the retrieval of ice crystal habit distributions inside cirrus clouds from upwelling far infrared spectral radiance observations. (May 2022) - Di Natale, Gianluca; Palchetti, Luca
Highlights: Introduction to the modelling of the cirrus clouds infrared spectral radiances by using mixtures of different crystal habits. Sensitivity study to the ice crystal habits of the upwelling infrared spectral observations simulated for the future ESA ninth Earth Explorer mission, named far-infrared outgoing radiation understanding and monitoring (FORUM). Presentation of the new approach to retrieve the coefficients of the crystal habit distribution. Abstract: In this paper a retrieval procedure of cirrus ice properties, based on the optimal estimation and the Levenberg–Marquardt iterative formula, is extended with a suitable non linear transformation of the cloud state vector parameters to include the crystal habit distribution in addition to the effective diameter and the optical depth. The cloud optical coefficients are linearly combined using different crystal shapes (solid columns, droxtals, hollow columns, bullet rosettes, aggregates and plates) to build up two different mixtures of habits to be used in the retrieval. This approach allows us to retrieve the coefficients of the habit crystals inside cirrus clouds by using upwelling far infrared spectral radiance measurements. The retrieval capability is shown by performing self-consistency tests using the Simultaneous Atmospheric and Cloud Retrieval (SACR) code and a set of 240 synthetic diverse observations in cloudy-sky generated by using realistic atmospheric scenarios (for mid-latitudes, tropics and poles) and the noise anticipated for the new far infrared sensor Far-infrared Outgoing Radiation Understanding and Monitoring (FORUM), which is planned to be launched as the ninth Earth Explorer (EE-9) by the European Space Agency (ESA) in 2026. The sensitivity of the retrieved crystal habit coefficients to parameters that are not retrieved, such as the surface temperature and emissivity, the cloud top and bottom heights, the ice fraction, the water vapour and temperature profiles, together with the biases caused by the cloud vertical and horizontal inhomogeneity, were also assessed and discussed in the paper.